An activist stage craft? Performative politics in the First British New Left (1956–1962). Issue 1 (2nd January 2022) - Scott-Brown, Sophie
ABSTRACT: The First British New Left (NL) (1956–1962) formed around two journals, The New Reasoner (NR) edited by E.P.Thompson and John Saville, and the Universities and Left Review (ULR) edited by Stuart Hall, Gabriel Pearson, Raphael Samuel and Charles Taylor. Both sought a 'new' socialism which, based on a loose concept of socialist humanism, restored the role of the individual and revitalised a popular left movement. Early commentators critiqued its lack of robust theory and organisational structure. More recently, others have proposed that, particularly amongst the ULR cohort, with this 'new' socialism emerged a 'new' activist politics. Building on this, I examine the ULR's activism as a performative politics which stressed active participation over theory and dissolved any distinction between means and ends. Whilst Thompson and Hall have tended to be considered the main protagonists in shaping this, I argue that it was Samuel, an experienced organiser, who was most responsible for shaping their early agenda. His role has been neglected because he wrote no 'position piece' but, appropriately for an activist politics, expressed his ideas through his actions. 'Reading' his performances, then, illuminates more fully both the scope and the limits of this activist politics.